Peculiarities of the formation of polyorganic dysfunction syndrome in experimental abdominal sepsis: kidney dysfunction - Sydorchuk, Ruslan; Stepan, Vasyl; Plehutsa, Oleksandr; Sydorchuk, Igor; Stepan, Bogdan (Journal of Education, Health and Sport, 2018)
Introduction: A steady increase in the incidence of the abdominal sepsis puts it into the top priority in terms of both medical and socio-economic significance. Multiple organ failure/dysfunction syndrome is one of the most important components of the pathogenesis of abdominal sepsis, determining the severity of the course, features of the clinical picture, mortality and outcome. The aim of the study is to determine the dynamics of changes in the functional state of the excretory system under the conditions of modeling of the AS in the acute experiment. Material and methods: The study included acute experiment on 38 white rats with abdominal sepsis modeled by intraabdominal injection of a patented mixture of both aerobic and anaerobic conditionally pathogenic microorganisms’ suspension and adjuvant substances influencing local host resistance. This study conforms to international and national standards of bioethics. Kidneys’ functional state was evaluated by determining a set of 46 functional markers. Results: All renal function parameters were significantly influenced by abdominal sepsis formation. At the beginning of the formation of the abdominal sepsis, the disruption of the transport of sodium ions is concentrated mainly in the area of the distal tubules. Subsequently, the zone of functional disorders also covers the proximal nephron. Conclusions: Formation of abdominal sepsis is characterized by a complex of physiological changes in the functional state of the kidneys, both adaptive- compensatory and pathological. Renal function undergoes phase changes under abdominal sepsis with predominantly adaptive and compensatory mechanisms dominating at the beginning with further involvement of kidneys’ components and formation of renal dysfunction.